Clonal Spread of Extended-Spectrum Cephalosporin-Resistant Enterobacteriaceae Between Companion Animals and Humans in South Korea - Hong, Jun Sung; Song, Wonkeun; Park, Hee-Myung; Oh, Jae-Young; Chae, Jong-Chan; Shin, Saeam; Jeong, Seok Hoon (Frontiers in Microbiology, 2019)
Extended-spectrum cephalosporin (ESC)-resistant Enterobacteriaceae is an increasingly important problem in both human and veterinary medicine. The aims of this study were to describe a comparative molecular characterization of Enterobacteriaceae carrying ESC resistance genes, encoding extended-spectrum β-lactamase (ESBL) and AmpC, isolated from human stool samples, rectal swabs from companion animals, and swabs from the environment of veterinarian hospitals in South Korea, and to examine their possible dissemination and transmission. The ESC resistance genes were identified by PCR and sequencing. Isolates with the predominant ESC resistance genes were assessed for their genetic relatedness by pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing. A total of 195 Escherichia coli and 41 Klebsiella pneumoniae isolates that exhibited ESC resistance were recovered on CHROMagar ESBL from human, companion animal, and the veterinary hospital environmental samples. In companion animals, most of the ESC resistance genes were blaCMY-2-like (26.4%), followed by blaCTX-M-55 (17.2%) and blaCTX-M-14 (16.1%), whereas blaCTX-M-15 (28.6%) was predominant in human samples. The epidemiological relatedness of isolates carrying ESC resistance genes, including 124 E. coli and 23 K. pneumoniae isolates carrying CMY-2-like, DHA-1-like, or/and CTX-M-type were analyzed by PFGE. The pulsotypes of five E. coli isolates (three from dogs and two from humans) carrying blaCMY-2-like, which were attributed to sequence type 405, from different veterinary clinics showed >85% similarity. Our results indicate direct transmission and dissemination of ESC-resistant Enterobacteriaceae between humans and companion animals.